Metals Challenged by Neutron and Synchrotron Radiation - Klaus-Dieter Liss (Metals, 2017)
In the past one and a half decades, neutron and synchrotron radiation techniques have come to the forefront as an excellent set of tools for the wider investigation of material structures and properties [1,2], becoming available to a large user community.[...]